Pengaruh Investasi Asing Langsung (FDI) Terhadap Pengangguran Usia Muda di Asia - Esis Prananika; Doni Satria (Universitas Negeri Padang, 2023)
This study discusses the effect of foreign direct investment (FDI) on youth unemployment in Asia which aims to determine the extent to which these factors affect it. In this study the variables used are foreign direct investment, economic growth, population growth, wages, exports and imports. The method used is a quantitative method with a descriptive research approach and associative research. The data used is secondary data from 1991 to 2019 with a sample of 19 countries in Asia obtained from related agencies. By using the panel data regression model and the best model is the Random Effect Model by testing it through the Chow test, Hausmant test and Lagrange test. Based on the results of the theoretical test, it shows that the output response of foreign direct investment and population growth has a significant negative effect on increasing youth unemployment in Asia, because an increase in foreign direct investment and population growth will reduce the number of unemployed. Meanwhile, the results of output wages and exports have a significant positive effect on youth unemployment in Asia, which means that any increase in wages and exports will affect an increase in youth unemployment. And economic growth output and imports have no effect on youth unemployment in Asia